Interfirm co-operation and learning within SME networks - two cases from the Styrian Automotive cluster - Michael Steiner; Christian Hartmann (European Regional Science Association (ERSA), 1998)
Recent publications in the cluster-related literature have shown that interfirm links imply the potential to foster higher forms of learning within clusters. Especially networks deserve in this context a particular focus of attention. The purpose of this paper is to show essential conditions that should be present at cluster level in order to enable such forms of learning between the firms. This will be done in order to give a first advice for public and semi-public cluster institutions to facilitate interfirm collaborations and cluster related activities. Two case-studies of SME-networks selected from Styrian clusters will give the opportunity to get deeper insights into the conditions that enable clusters to bring forth double loop learning activities. In a first step particular criteria for the presence of double-loop learning will be established. In a second step the conditions for this specific type of learning will be dealt with. Among the categories of conditions that will be examined in detail are the relations and interactions in the network, the types of joint projects carried out between the firms and the specific organizational culture that prevails at the individual firm level. Key words: SME-networks, learning, organizational culture.
Keywords: 330